Russia’s Turn to the East: Prospects for Cooperation with Greater Eurasian Countries - A. V. Nikolaenko; E. N. Kurkina (Евразийская интеграция: экономика, право, политика, 2025)
Aim and tasks. The study is aimed at studying the prospects of the Asian vector of Russia’s foreign policy in the context of the implementation of the “Turn to the East” policy.   The purpose of the article is to study the current state of Russia’s cooperation with Asian countries within the framework of the implemented “Turn to the East” policy and to identify its future prospects.   The authors chose the Asia-Pacific region as the main object, since today it seems to be an important strategic direction of the Russian Federation. To identify the main trends in Russia’s interaction with Asian countries, the dynamics of Russia’s economic cooperation with leading states that are the country’s main partners in difficult geopolitical conditions.   Methods. When writing the article, the authors used general scientific methods. First of all, analysis and synthesis; system and comparative analysis; historiographic methods: the principle of historicism, the chronological method. To analyze Russia’s trade turnover with Asian countries, the statistical and comparative methods were used. To study the reasons for the turn ofRussia’s foreign policy to the East, the principle of historicism and the chronological method were used.   Results and conclusions. Having analyzed various aspects of the “Eastern” policy, its influence on the successful development of relations between Russia and the Asia-Pacific countries (including its main strategic partner, China) was revealed. Moreover, the implemented policy has a positive effect on Russian-Asian investment cooperation in the development of the Far Eastern region, and also makes a significant contribution to the formation of a new global multipolar system. Russia and China are strengthening cooperation in trade, scientific and military technologies, culture, energy, healthcare, and others. Strengthening interaction with friendly Asian countries helps diversify Russia’s ties in the face of turbulence.